Masters of the cyber-universe. (Economist, 2013)
The article discusses state-sponsored computer hacking in China, with information on cyberattacks on a wide variety of U.S. targets including businesses, media outlets, and human rights groups. Topics include the organisation and scale of cyberattacks originating in China, the lack of retribution from targets, and the open recruitment of computer hackers by the Chinese People's Liberation Army (PLA).